FORMATIVE FEEDBACK IN MATHEMATICS EDUCATION: A SYSTEMATIC REVIEW OF RESEARCH INSTRUMENTS AND LEARNING OUTCOMES - Nur Farhanah Mardhiah Mohd Zaini; Nurul Akmal Mohamed; Nur Idalisa Norddin; Nurul Huda Mohamed; Nurul Farihan Mohamed (JP2MS, 2025)
Formative feedback is an important aspect in mathematics teaching since it helps students to build mathematical thinking, enhance conceptual knowledge, and work toward better learning results. Although it is crucial, a consensus on the most effective feedback practices and research instruments to be used in the mathematics setting is limited. Numerous research studies implement various tools without a clear reference to mathematical capabilities, which leads to inappropriate research results and difficulties in the classroom. The research was based on a systematic literature review (SLR) to investigate the current application of different research instruments to measure formative feedback in mathematics education and its effect on student learning outcomes. Using ProQuest, Scopus, and EBSCOhost as the sources of data collection on the guidance of PRISMA protocols, key search words that were used were formative feedback and mathematics learning outcomes. The number of selected articles was 21, which was analyzed with the help of thematic and descriptive approaches. The review found six broad types of tools to provide formative feedback, namely, student feedback tools, gamification frameworks, structured frameworks, classroom artifacts, digital tools, and observation protocols. Student feedback tools and digital tools were most used among them as they also indicate a transition to interactive and personalized learning environments. These tools were often associated with six major learning outcomes, such as conceptual understanding, engagement, self-regulation, critical thinking, emotional responses, and motivation, with conceptual understanding and engagement being the most affected. Overall, the results suggest that formative feedback is an essential tool in improving mathematics learning yet also indicates the gap in the correspondence between the instruments of feedback and the specific mathematical skills. The study requires additional research to determine better links and create more productive and evidence-based feedback practices.